Training in higher education in design and the pandemic crisis: Lived experiences - Caeiro Guerreiro, Maria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The COVID19 pandemic situation provided the adoption of new educational strategies in higher education, and a challenge in the performance of teachers and students. We will thus identify the strategies taken in the Communication Design IV discipline, of the Communication Design course, University of Algarve. To carry out the work, we used a qualitative methodology, intensive analysis and case study, document analysis, observation and interviews. We verified that the greater focus was on the students' needs, providing them with more autonomy and the acquisition of new skills, in the professional scope.